Mapping the terminology of the early rescue chain to the Foundation of ICD-11: Registered report protocol - Masresha Derese Tegegne; Samson W. Tu; Islam Ibrahim; Ronald Cornet; Sharareh Rostam Niakan Kalhori; Thomas M. Deserno (PLoS ONE, 2026)
Background The World Health Organization (WHO) emphasizes digital technologies as a key accelerator for strengthening health emergency preparedness and response. One such application is the early rescue chain (ERC), which coordinates automated alerting, responding, and clinical systems. However, current ERC implementations primarily rely on spoken language and lack standardized terminology. The ERC Terminology (ERC_T) defines the minimum set of concepts required for automated and standardized ERC information exchange. The International Classification of Diseases, 11th Revision (ICD-11) extensively covers adverse events in its sections: “External causes of morbidity or mortality” and “Dimensions of external causes”. However, there is no comprehensive mapping of ERC_T to the ICD-11 Foundation (ICD-11_F), the terminological resource from which the successor to ICD-10, ICD-11 Mortality and Morbidity Statistics (MMS), is derived. Therefore, we aim to: (I) assess semantic relationships between ERC_T and ICD-11_F; (II) evaluate the overall mapping quality; and (III) identify missing concepts and semantic gaps between ERC_T and ICD-11_F. Methods We will select ICD-11_F as the target of the mapping because of its greater specificity and its structure as a terminology rather than a classification that is constrained to a single-parent monohierarchy with residual categories. We will systematically map concepts from ERC_T to ICD-11_F using predefined mapping criteria and procedures. The mapping process addresses two complementary aspects of semantic alignment. First, we will classify the semantic relationship between an ERC_T concept and an ICD-11_F entity using HL7 FHIR ConceptMap relationships. Second, we will evaluate the quality of each mapping using ISO 21564:2025 (MapQual) measures, which provide a structured assessment of how well the ICD-11_F entity represents the ERC_T concept. Two coders will independently conduct the mapping following predefined mapping procedures. We will assess intercoder agreement using percentage and Krippendorff’s alpha (α), and will resolve disagreements through structured consensus or, if unresolved, by a senior expert.